2010
DOI: 10.1371/journal.pone.0009481
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Angiopoietins Is Associated with Placental Malaria and Low Birth Weight

Abstract: BackgroundPlacental malaria (PM) is associated with adverse pregnancy outcomes including low birth weight (LBW). However, the precise mechanisms by which PM induces LBW are poorly defined. Based on the essential role of angiopoietin (ANG)-1 and -2 in normal placental vascular development, we hypothesized that PM may result in the dysregulation of angiopoietins and thereby contribute to LBW outcomes.Methods and FindingsIn a mouse model of PM, we show that Plasmodium berghei ANKA infection of pregnant mice resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 56 publications
3
57
0
2
Order By: Relevance
“…Subsequent studies, however, have all identified Ang-1 as a more consistent diagnostic biomarker in malaria, discriminating between cerebral malaria and uncomplicated malaria in Thai adults and Ugandan children, between cerebral, severe, and uncomplicated malaria in Thai adults, and between cerebral malaria with retinopathy and febrile, non-malarial causes of decreased level of consciousness in Malawian children 28 - 30 . Furthermore, decreased Ang-1 was associated with P. falciparum malaria in pregnancy, while an increased Ang-2:Ang-1 ratio was associated with both placental malaria and low birth weight infants 31 . As a prognostic marker, the plasma Ang-2 concentration at admission to hospital has been shown to correlate with mortality in children with cerebral malaria in two separate studies 32 , 33 …”
Section: Mediators Of Endothelial Function: Angiopoietin-1 and -2mentioning
confidence: 91%
“…Subsequent studies, however, have all identified Ang-1 as a more consistent diagnostic biomarker in malaria, discriminating between cerebral malaria and uncomplicated malaria in Thai adults and Ugandan children, between cerebral, severe, and uncomplicated malaria in Thai adults, and between cerebral malaria with retinopathy and febrile, non-malarial causes of decreased level of consciousness in Malawian children 28 - 30 . Furthermore, decreased Ang-1 was associated with P. falciparum malaria in pregnancy, while an increased Ang-2:Ang-1 ratio was associated with both placental malaria and low birth weight infants 31 . As a prognostic marker, the plasma Ang-2 concentration at admission to hospital has been shown to correlate with mortality in children with cerebral malaria in two separate studies 32 , 33 …”
Section: Mediators Of Endothelial Function: Angiopoietin-1 and -2mentioning
confidence: 91%
“…Animal protocols were approved by the Toronto University Health Network Animal Care Committee and performed in accordance with the Canadian Council on Animal Care Guidelines. We used a previously validated mouse model of PM that replicates key pathogenic features of human PM, including placental parasite sequestration, placental inflammation, spontaneous abortion, and fetal growth restriction (Silver et al, 2010). Eight-to ten-week-old Balb/c female mice were obtained from The Jackson Laboratories Inc. (Bar Harbor, ME) and maintained on a 12-hour light/dark cycle with ad libitum access to standard rodent chow and water.…”
Section: Methodsmentioning
confidence: 99%
“…Females were mated and checked for the presence of a vaginal plug (GD1). Cryopreserved PbA strain malaria (MR4; American Type Culture Collection, Manassas, VA) was passaged through a male Balb/c mouse as previously described (Silver et al, 2010). On GD13, dams were inoculated with 10 6 PbA-infected erythrocytes in RPMI (Sigma-Aldrich, Oakville, ON, Canada) via tail vein injection.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma levels of Ang-2 and ratio of Ang-2/Ang-1 are clinical biomarkers that can predict fatal cerebral malaria [57][58][59]. Dysregulation of Angs is associated with placental malaria and low birth weight [60]. The association of increased Ang-2 and decreased nitric oxide are poor outcomes in severe P. falciparum [61][62].…”
Section: The Genomic Factors Associated With Vitamin D In Malariamentioning
confidence: 99%